Algal swamp, marginal and shallow evaporitic lacustrine lithofacies from the late Devonian - early Carboniferous Albert Formation, southeastern New Brunswick, Canada - Carter, D.; Pickerill, R. (Atlantic Geology, 1985)
The Albert Formation in the Moncton Subbasin of southern New Brunswick was essentially deposited in a complex series of spatially and temporally inter-related alluvial fan, fluvial-deltaic and "deep" water lacustrine depositionat environments and which have all previously been described in detail. Herein we describe three depositional environments and their lithofacies which have not previously been described in any great detail, but constitute an integral part of the succession. These are the algal swamp, marginal (shoreface and carbonate mudflat) and shallow evaporitic lacustrine environments and their lithofacies. Algal swamp lithofacies are characterized by kerogenous mudstones and inorganically precipitated nodular and phylloid or stromatolitic algal carbonates. Marginal lacustrine lithofacies are represented by two distinctive assemblages, namely carbonate mudflat and shoreface lithofacies. The former are characterized by dolomitic shales and interbeds of argillaceous limestones, aphanitic dolostones, siltstones and rare kerogenous and sub-kerogenous mudstones. The latter are characterized by 0.5-lm thick sandstones and interbedded shales or mudstones. Both exhibit evidence of ephemeral exposure. Evaporitic lacustrine lithofacies are characterized by halite, gypsum, glauberite, anhydrite and dolostone with associated shales and siltstones containing molds of evaporite minerals replaced by calcite. Using surface and available drill data an assessment of the spatial distribution, both within the Moncton Subbasin itself and with respect to associated depositional environments, of these lithofacies is made.